Herbal extract-based phytocosmetic as potential tyrosinase inhibitors Antioxidants, anti-inflammatory and skin-whitening cosmetic intgredients. - Hadil Heddadj; Meriem Mensouri (. جامعة الوادي.Université d'EL-Oued., 2025)
This study aims to evaluate the therapeutic potential of plant extracts from three species: Cyperus rotundus Linn, Glycyrrhiza glabra, and Hibiscus sabdariffa, with a focus on their chemical composition and biological activities, particularly their tyrosinase inhibitory activity, which represents an important pharmacological target in the development of natural skinlightening cosmetic products. The study begins with a preliminary phytochemical screening of the plant extracts to detect the presence of secondary metabolites such as flavonoids and polyphenols. Subsequently, the biological activities of the extracts were evaluated using in vitro assays, including antioxidant, anti-inflammatory, antimicrobial, and tyrosinase inhibition activities. on the other hand, The results showed good biological activity compared with the chosen standards. In addition, in silico tools by Molecular docking were employed to predict binding affinity between active compounds and tyrosinase enzyme and cyclooxygenase 2, alongside assessment of physicochemical properties, drug-likeness (Lipinski's Rule), bioavailability, and potential toxicity of selected compounds by swiss ADME and ProTox. The results reveal druglike properties of different compounds, moreover the values of k and G show a spontaneous electrostatic type interaction. Overall, this study highlights the significant potential of these plant species as natural sources of bioactive compounds with promising applications in the cosmetic industry, particularly for skin-whitening formulations. It also underscores the importance of integrating both experimental and computational approaches for a comprehensive and accurate evaluation of such compounds.
Toxicology
Keywords: plants extract; tyrosinase inhibition; molecular Docking; swiss ADME; whitening formulation; cyclooxygenase